Educational inputs and outcomes before the transition from communism - John Beirne; Nauro F. Campos (Institute for the Study of Labor (IZA), 2006)
Conventional wisdom suggests that the stocks of human capital were one of the few positive legacies from communism. However, if factories under communism were so inefficient, why would the education system not have been? Using the education production function approach and new data on educational inputs and outcomes from 1960 to 1989, we find evidence suggesting that the official human capital stocks figures were over-estimated during the communist period. In other words, we find that the official human capital stock numbers are significantly higher than those predicted not only in relation to countries at similar levels of development, but also on the basis of educational systems with comparable features and efficiency levels.
urn:nbn:de:101:1-20080509117
Keywords: 330